POLA LUKA PADA KEMATIAN YANG DISEBABKAN OLEH KEKERASAN TAJAM DI RS. BHAYANGKARA MEDAN - DITA AMBARDINI JUWITA SUDARTO; ABDUL GAFAR PARINDURI (LP2MTBM MAKARIOZ, 2021)
Wounds on violence caused by objects that have sharp or pointed sides are categorized as injuries caused by sharp objectviolence. Types of wounds caused by violence that can be identified as stab wounds, cuts and slashes. To see how thepattern of injuries to death caused by violence at Bhayangkara Hospital Medan is described. This research is a retrospectivedescriptive study with 197 samples of victims of death due to violence as seen from the Visum et Repertum from the autopsyresults in 2018-2019. Univariate analysis was performed on each research variable and the category of frequencydistribution of each variable was expressed as a proportion. It is known that the age distribution of victims is generally <30years old (55.8%). For types of wounds, stab wounds (67%), sliced wounds (11.2), cut wounds (21.8). It is known that thelargest distribution of wound locations is the chest (31%).